Peran Kereta Rel Listrik (KRL) Jogja-Solo sebagai Akselerator Transformasi Kawasan di Pusat Kota (Kasus: Stasiun Tugu Yogyakarta) - Ramadhani, Pawiloy; Swasto, Deva Fosterharoldas (Jurnal Peweka Tadulako, 2025)
The operation of the Jogja-Solo Commuter Line (KRL) since 2021 has been a significant transportation infrastructure intervention connecting Yogyakarta and Surakarta. Tugu Station, as a central hub in the heart of Yogyakarta, presents a unique case where the impact of this infrastructure does not create new growth but rather potentially accelerates the dynamics within an established commercial and tourism area. This study aims to analyze the role of the KRL in the process of social, economic, and spatial transformation around Tugu Station, Yogyakarta. Using a qualitative method with a case study approach, data were collected through in-depth interviews with local residents, business owners, and commuters, reinforced by field observations within an 800-meter radius of the station. The findings show that the presence of the KRL acts as a significant accelerator of change. Spatially, an increase in land-use intensity occurred, marked by the conversion of residential properties into commercial enterprises and a rise in building density. Economically, the emergence of new business opportunities in the service and trade sectors has boosted local economic activity, albeit accompanied by increased competition. These changes also influenced social dynamics through shifts in daily mobility patterns and the emergence of diverse perceptions regarding the area's comfort and safety. Collectively, these findings illustrate a process of functional densification in the area, which has also triggered business competition and an economic shift among local residents. In conclusion, the role of the KRL at Tugu Station is identified as extending beyond its function as a transportation provider, acting instead as an agent that contributes to reshaping the dynamics of the city center. This finding implies the importance of adaptive spatial planning policies to manage growth and maintain a balance between commercial, tourism, and social functions in key transit areas.